NurkhairatArniman |KepemimpinanKepalaSekolah... 44 KEPEMIMPINAN KEPALA SEKOLAH SESUAI PANDANGAN ISLAM DI ERA MODERN - Arniman, Nurkhairat; Yustina, Luli Sari; Basit, Abdul (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2024)
The aim of this study is to examine a leadership of school principals in the context of education whether is crucial, especially in the modern era. Person who asked as a good manager. It is filled with challenges and changes. The leadership of school principals based on Islamic perspectives, emphasizing values of justice, integrity, and responsibility. In the digital and informational era, school principals are required to be adaptive and innovative leaders while adhering to Islamic principles.This research employs a qualitative method with an in-depth analysis of the characteristics of leadership in accordance with Islamic teachings. The findings indicate that principals who applied Islamic values can create a conducive and competitive learning environment. Additionally, this study provides recommendations for the future development of school leadership, while considering the role of religionin shaping the character and ethics of leaders in the field of education that very give significance in the modern era.